Patterns of hospital admission in 54 501 patients with epistaxis over a 20‐year period in Scotland, UK. (8th August 2018) - Douglas, Catriona M.; Tikka, Theofano; Broadbent, Benedict; Calder, Nick; Montgomery, Jenny
Abstract : Background: Epistaxis affects most people over their lifetime. It is the commonest ear, nose and throat emergency. Hospital admission and socio‐economic deprivation have been associated with mental health disorders, respiratory illness and with emergency hospital admissions. Low socio‐economic status has never previously been associated with epistaxis, a common reason for admission to ear, nose and throat departments throughout the UK. Methods: Demographics from Information Services Division Scotland were analysed over a period of 20 years. This focused on gender, number of admissions, number of bed days, socio‐economic deprivation (Scottish Index of Multiple Deprivation) and mortality within 1 year. Results: Data from 54 501 patients were assessed. Admission numbers and length of stay have significantly decreased ( P < 0.0001). Males are more frequently affected ( P = 0.001). Admission numbers were higher for patients in more deprived areas ( P < 0.001). Mean duration of stay has decreased by 1 bed day. Surgical intervention of epistaxis has increased significantly ( P < 0.001). There is an associated 1‐year mortality rate of 9.8% following epistaxis. Conclusion: There has been a significant decrease in hospital admissions and length of hospital stay in patients admitted with epistaxis over the past 20 years. There is a significant association with deprivation and epistaxis admission.